Internal capital markets and the funding of subsidiaries of multinational banks - Gulamhussen, M. A.; Lavrador, I. M. M. (International Finance, 2014)
We study the factors that determine the debt funding of subsidiaries of multinational banks. Our findings indicate that the funding of subsidiaries is determined by the internalization advantages of the parent bank and the home country, in addition to the characteristics of the subsidiary and the host country. Subsidiaries of multinational banks adjust the level of their funding by virtue of their affiliation with their parent’s multinational network. Multinational banks may exploit their internalization advantages to secure funding via subsidiaries. Our findings suggest that gaps in regulation and supervision between host and home countries have the potential to undermine the sound functioning of the global financial system.